Effects of amyloid peptides on A-type K+ currents of Drosophila larval cholinergic neurons. - Kidd, J; Brown, L; Sattelle, D (2006)
Accumulation of amyloid (Abeta) peptides has been suggested to be the primary event in Alzheimer's disease. In neurons, K+ channels regulate a number of processes, including setting the resting potential, keeping action potentials short, timing interspike intervals, synaptic plasticity, and cell death. In particular, A-type K+ channels have been implicated in the onset of LTP in mammalian neurons, which is thought to underlie learning and memory. A number of studies have shown that Abeta peptides alter the properties of K+ currents in mammalian neurons. We set out to determine the effects of Abeta peptides on the neuronal A-type K+ channels of Drosophila. Treatment of cells for 18 h with 1 microM Abeta1-42 altered the kinetics of the A-type K+ current, shifting steady-state inactivation to more depolarized potentials and increasing the rate of recovery from inactivation. It also caused a decrease in neuronal viability. Thus it seems that alteration in the properties of the A-type K+ current is a prelude to the amyloid-induced death of neurons. This alteration in the properties of the A-type K+ current may provide a basis for the early memory impairment that was observed prior to neurodegeneration in a recent study of a transgenic Drosophila melanogaster line over-expressing the human Abeta1-42 peptide.